Hubungan ekspresi programmed death-ligand 1 (PD-L1) dengan profil klinikopatologi karsinoma nasofaring undifferentiated subtype di RSUP Prof. dr. I.G.N.G. Ngoerah Denpasar - Megadasari, Anak Agung Prami; Sumadi, I Wayan Juli; Dewi, I Gusti Ayu Sri Mahendra (Intisari Sains Medis (ISM) (Manado), 2024)
Background: Nasopharyngeal Carcinoma (NPC) is a malignant neoplasm originating from the surface epithelium of the nasopharyngeal mucosa, which shows squamous differentiation. NPC is often associated with Epstein Barr Virus (EBV) infection, leading to increased PD-L1 expression. This study aims to determine the relationship between PD-L1 expression in tumor cells and immune cells and the clinicopathological profile of NPC. Methods: This study used a cross-sectional analytical study design. Thirty-three samples were taken from paraffin blocks of patients who underwent initial biopsy at Prof. I.G.N.G Ngoerah Hospital between 2019 and 2022. Samples were collected using consecutive sampling techniques and subjected to immunohistochemistry (IHC) staining with PD-L1 antibody (clone 28-8, CellMerQ). HE slides were reviewed to assess histopathological types. The results of PD-L1 IHC staining, including tumor cells (TCS) and immunoreactive score (IRS), were correlated with NPC clinicopathological variables, including age, gender, histopathological type, and stage. Statistical analysis was performed using Chi-Square and Fisher Exact tests, with a significance level of p<0.05 and a 95% confidence interval. Results: The mean age of subjects in this study was 53.58 years, with a median value of 55 years; 48.5% were aged <55 years, and 51.5% were aged ≥55 years. Twenty-three individuals (63.7%) were male, and 10 (27.3%) were female. There was a significant association between PD-L1 expression in tumor cells and patient age (p = 0.008). Significant associations were found between PD-L1 expression in tumors and immune cells with clinical stage (p = 0.024 and p = 0.024, respectively). There was a significant association between PD-L1 expression in tumor cells and PD-L1 expression in immune cells (p = <0.001). No significant associations were found between PD-L1 expression in immune cells and age (p = 0.055) and between PD-L1 expression in tumor cells and immune cells with gender (p = 0.105 and p = 0.105, respectively). Conclusion: There is a significant association between PD-L1 expression in tumor cells and patient age and clinical stage. There is also a significant association between PD-L1 expression in immune cells and the clinical stage. Additionally, there is a significant association between PD-L1 expression in tumor cells (TCS) and PD-L1 expression in immune cells (IRS).